Exosomes From miR-19b-3p-Modified ADSCs Inhibit Ferroptosis in Intracerebral Hemorrhage Mice - Yi, Xia; Tang, Xiangqi (Frontiers in Cell and Developmental Biology, 2021)
Abstract Objectives: Effective treatments for intracerebral hemorrhage (ICH) are limited until now. Ferroptosis, a novel form of iron-dependent cell death, is implicated in neurodegeneration diseases. Here, we attempted to investigate the impact of exosomes from miR-19b-3p-modified adipose-derived stem cells (ADSCs) on ferroptosis in ICH. Methods: Collagenase was used to induce a mouse model of ICH and hemin was used to induce ferroptosis in cultured neurons. Exosomes were isolated from mimic NC- or miR-19b-3p mimic-transfected ADSCs (ADSCs-MNC-Exos or ADSCs-19bM-Exos, respectively) and then administered to ICH mice or hemin-treated neurons. ICH damage was evaluated by assessing the neurological function of ICH mice and cell viability of neurons. Ferroptosis was evaluated in mouse brains or cultured neurons. The interaction between miR-19b-3p and iron regulatory protein 2 (IRP2) 3’-UTR was analyzed by performing luciferase reporter assay. Results: Ferroptosis occurred in ICH mice, which also exhibited decreased miR-19b-3p and increased IRP2 expression. IRP2 was a direct target of miR-19b-3p, and IRP2 expression was reoressed by ADSCs-19bM-Exos. Importantly, ADSCs-19bM-Exos effectively attenuated hemin-induced cell injury and ferroptosis. Moreover, ADSCs-19bM-Exos administration significantly improved neurologic function and inhibited ferroptosis in ICH mice. Conclusion: Exosomes from miR-19b-3p-modified ADSCs inhibit ferroptosis in ICH mice.